Foreign Records on the Malay Archipelago Through Vietnam's Perspective - Ku, Boon Dar (2016)
This paper attempts to trace the early history of the Malay Archipelago with Vietnam based on the records of Vietnam’s emissaries. A specific focus is given to the 19th century due to the dynamic political and economic relations with the Western powers, witnessed in the maritime activities of the Malay Archipelago. The developments of capitalism and trade encouraged the Western colonialist to tap into the wealth of the Malay Archipelago’s natural resources. In addition, Vietnam sent about 40 missions abroad in its diplomatic effort to establish ties with foreign countries including the states in the Malay Archipelago. However, the records of the voyages of Vietnam’s envoys on the lives of the people in the Malay Archipelago have been partially explored by scholars. They are rarely mentioned in historical resources. Therefore, this paper will explore the records of Hai Trinh Chi Luoc (A Summary Report of Sea Journey) and Tay Hanh Kien Van Ki Luoc (An Account of Journey to the West) which were written by Phan Huy Chu and Ly Van Phuc respectively. The paper suggests that both sources can be utilised by the local scholars to reconstruct the history of the Malay Archipelago which has been heavily dependent on Western sources.